2015
DOI: 10.1038/npp.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Exposure Combined with HIV-1 Disease or gp120 Expression: Comparison of Learning and Executive Functions in Humans and Mice

Abstract: Methamphetamine dependence is a common comorbid condition among people living with HIV, and may exacerbate HIV-associated neurocognitive disorders. Animal models of neuroAIDS suggest that the gp120 protein may also cause cognitive impairment. The present work evaluated the separate and combined effects of HIV/gp120 and methamphetamine on learning and executive functions in both humans and transgenic mice. Human participants were grouped by HIV serostatus (HIV+ or HIV − ) and lifetime methamphetamine dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 57 publications
2
43
0
Order By: Relevance
“…Impairments in the response to pleasure (i.e., reward deficits or anhedonia) represent a key feature of depression (Pizzagalli et al, 2005, Der-Avakian et al, 2014), and may explain increased rates of major depression/mood disorders after HIV infection and methamphetamine dependence (Kesby et al, 2015, Panee et al, 2015). In HIV-infected subjects, depressed moods, methamphetamine and nicotine dependence have all been associated with decreased likelihood to initiate highly active antiretroviral therapy (HAART) (Tegger et al, 2008, King et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairments in the response to pleasure (i.e., reward deficits or anhedonia) represent a key feature of depression (Pizzagalli et al, 2005, Der-Avakian et al, 2014), and may explain increased rates of major depression/mood disorders after HIV infection and methamphetamine dependence (Kesby et al, 2015, Panee et al, 2015). In HIV-infected subjects, depressed moods, methamphetamine and nicotine dependence have all been associated with decreased likelihood to initiate highly active antiretroviral therapy (HAART) (Tegger et al, 2008, King et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we have previously shown that expression of HIV-associated gp120 protein increases the sensitivity to methamphetamine and exacerbates cognitive impairments in mice (Kesby et al, 2014, Kesby et al, 2015). The viral TAT protein has also been implicated in HIV-induced neuropathology given its central role in the pathogenesis of HIV infection (for review, (Li et al, 2009)).…”
Section: Introductionmentioning
confidence: 99%
“…Mice were 4–5 months old at the beginning of study procedures and 9–10 months old at time of MRI, (see below). These mice were previously tested in a battery of cognitive tasks (Kesby et al, 2015a; Kesby et al, 2015b). …”
Section: Methodsmentioning
confidence: 99%
“…While the neurotoxic effects of METH have been typically induced by an acute “binge” procedure (4 injections of high doses in drug-naïve rodents; Davidson et al, 2001), it has been postulated that the inclusion of an escalating dose pretreatment regimen represents a more accurate simulation of the gradual dose progression in human abusers (Segal and Kuczenski, 1997). Prior work indicated that inclusion of this escalation paradigm attenuates the hyperthermic effects of higher METH doses in rats, while still inducing neuropathological and behavioral effects in both rats and mice (Henry et al, 2013; Kesby et al, 2015a; Kesby et al, 2015b; Kuczenski et al, 2007). Mice were treated three times per day (10:00; 13:15; 17:30 h) for 14 days with vehicle (saline; n=13) or escalating doses of METH (n=14), starting with 0.1mg/kg and increasing to 4.0mg/kg, with a stepwise increase of 0.1mg/kg per injection.…”
Section: Methodsmentioning
confidence: 99%
“…Data from catalepsy and locomotor tests, plasma corticosterone assays (baseline and CAR challenge as separate analyses) and HPLC assays were analysed with two-way ANOVA followed by Tukey's post hoc tests. For CAR training data, survival curve analysis was performed using Kaplan-Meir technique and log-rank (Mantel-Cox) test as described previously (Kesby et al 2015). Pearson's Chi-Square analyses were performed to compare the failure rates of CAR learning in different treatment groups.…”
Section: Discussionmentioning
confidence: 99%